Knowledge, boundaries, and bodies: Social construction between medical sociology and science and technology studies. Issue 10 (20th August 2021) - Shaffer, Jonathan D.
Abstract: Medical sociology and science and technology studies (STS) emerged from different positions, but often closely related concerns, within the broad discipline of sociology. Their interface and areas of overlap have mostly been shaped by theoretical positions broadly considered "social constructionist." Taken together, these perspectives provide empirical and theoretical tools to analyze important questions about how social inequalities, forms of scientific knowledge, and patterns of human health come to be produced and feedback into one another. Examining their intersection enables sociological questions such as: How is medical and public health scientific knowledge produced, stabilized, and taken as fact? How are scientific facts about health and illness used, experienced, and challenged? What is the relationship between health inequalities and public health or medical knowledge? This article seeks to briefly trace the important contributions that social constructionist research has made at the interstices of medical sociology and STS, further clarifying the history, points of intersection, and areas of diversion between them. The current COVID‐19 pandemic has unveiled the political struggles that constitute public health scientific knowledge and circulation. The interface between STS and medical sociology can help us to make sense of the interrelationships between politics, power inequalities, and public health scientific knowledge.